Tingkat Pengetahuan Guru PAUD tentang Kurikulum 2013 - Dwi Noviana; Titin Faridatun Nisa’; Muhammad Busyro Karim (Universitas Trunojoyo Madura, 2019)
This quantitative-descriptive research describes knowledge level of Early Childhood Education teachers about 2013 curriculum in whole Pademawu kindergartens, Pamekasan regency. Requirement analysis tests use kolomogorov-smirnov normality test. The sample is taken by nonprobability sampling and purposive sampling, involving 73 Early Childhood Education teachers. Technique of collecting data are objective test in the form of true or false (T-F), interview, and documentation. Based on analysis, H0 is denied and Ha is accepted in hypothesis test. Based on the findings, the knowledge level about 2013 curriculum in whole Pademawu kindergarten, Pamekasan is well, 87.71%. Finding on remembering factor (C1) showed most of them were categorized well, 94.38%; understanding (C2) categorized well, 85.57%; and applying (C3) categorized well, 70.37%. It can be concluded the knowledge level of the teachers about 2013 curriculum is well.